PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP PEMBELAJARAN MATEMATIKA SISWA KELAS X SMK PGRI 7 SURABAYA - Sebastianus Mere (Universitas PGRI Adi Buana Surabaya, 2016)
Background of this research is caused by the lower of the education quality that is the used of unappropriate model by the teachers in teaching learning mathematics in classroom, so it makes the result of the teaching learning, kognitive ability, efective ability, and psikomotoric abilty are not ballance. Based on the explanation above, the teachers are suggested to create the education environment by using the appropriate model in teaching learning mathematics that is Cooperative STAD Model. This model is more presure the students to look for the solves in working in group with their friends. The statement of the problem in this research is “how is the student activities, responses, and the completeness of students’ learning after the using of Cooperartive STAD Model at the second grade students of SMK PGRI 7 Surabaya”. The purpose is to describe the students activities, responses, and the completeness of students’ learning if the Cooperative STAD Model is attached at the second grade students of SMK PGRI 7 Surabaya. Data analysis techinique in this research is descriptive kualitative with the data source is the second grade students of SMK PGRI 7 Surabaya that number in 40 students and data collection technique is using observation, questionnaire, and post-test. Based on the research finding, it can conclude that the result of the students’ learning at the second grade students of SMK PGRI 7 Surabaya with the relation as the topic in teaching learning are completeness with the 95 % as clasical completeness percentage. The students’ activities are more active with the percentage 87. 65% that higher than the students are not active with percentage 12. 35% and the students’ responses at the teaching learning show the positive responses with the percentage 93.08%. Keywords: Cooperative STAD Model